Living Emergency: Israel's Permit Regime in the Occupied West Bank - Berda, Yael (Stanford University Press, 2017)
Cover -- Contents -- Prologue -- 1. Dangerous Populations -- 2. Perpetual Emergency -- 3. Labor of Uncertainty -- 4. Effective Inefficiency -- Epilogue -- Acknowledgments -- Notes.